Correction: Dissection of mitogenic and neurodegenerative actions of cystine and glutamate in malignant gliomas (Oncogene, (2011), 30, 1, (43-53), 10.1038/onc.2010.391) - Savaskan, N. E.; Seufert, S.; Hauke, J.; Tränkle, C.; Eyüpoglu, Ilker Yasin; Hahnen, E. (Oncogene, 2023)
Following the publication of the article the authors were informed by the scientific community that, regarding the MTT and LDH data presented in the manuscript, an inappropriate statistical test for outliers was used, which was not specified in the “Materials and methods” section. Our correction is aimed to extend the “Materials and methods” section in which the description of the statistical test for outliers was missing. Our re-analyses resulted in changes of some of the mean values, which differ from those presented in the manuscript. Our correction is aimed to address these changes. Cell proliferation and cytotoxicity assays were repeated at least eight times (MTT assay, n=8), or six times (LDH assay, n=6), respectively, using 96-well plates (500 cells per well; total volume 300 μl per well). For each 96-well plate experiment, at least four wells without cells and test compound(s) we used as blanks. Signals were quantified using a Tecan Safire2 microplate reader (Tecan, Zurich, Switzerland). Signals we tested for outliers using the two sided Iglewicz and Hoaglin’s robust test for multiple outliers using the recommended Z-score of 3.5 (available at contchart.com/outliers. sppx). Signals which were identified as outliers by Iglewicz and Hoaglin’s robust test for multiple outliers were removed from further analyses. Regarding the published data, several corrections have to be made. The following mean values deviate by at least five percentage points from the published mean values or the presented significance level changed.
CRIS-Team Scopus Importer:2023-03-03